The relationship between anxiety and COVID‐19‐associated isolation and lifestyle changes in the university community as a result of the SARS‐CoV‐2 pandemic - Saceanu Leser, Felipe (2023)
In 2020, the novel severe acute respiratory syndrome coronavirus outbreak emerged as apublic health emergency. Three years later, we are still assessing the effects caused by thecoronavirus disease (COVID‐19) and by the lifestyle changes due to prevention measures,like social isolation. Here, we assessed the profile of both the anxiety screening scores andanthropometric variables in the university community, associated with the isolation due tothe COVID‐19 pandemic. We analyzed social and epidemiological associated factors foranxiety and weight change to address and better identify the physical and mental conditionsaggravated during the pandemic. This is a cross‐sectional study based on the 7‐itemGeneralized Anxiety Disorder Scale questionnaire applied virtually to university students andprofessors in the State of Rio de Janeiro (n= 480). In our population cohort, we showed thatthe majority of individuals showed moderate to severe anxiety and increased body weightduring the COVID‐19 pandemic. The major demographic associated factors for higheranxiety levels were young age, female gender, and low family income. The main modifiableassociated factors for both anxiety and weight gain were the negative changes in livinghabits. In addition, there was a trend toward severe anxiety and greater weight change inpeople with increased time in social isolation. In view of these results, we suggest that bad habits, adopted during the COVID‐19 pandemic, were the main reason for the high anxietylevels found in the studied population.